Destination Hinterland:In's and Out's of Branding - Siraj, Sadaf; Sharma, Pratima (Indian Journal of Marketing, 2009)
With about 75% of population living in the villages and generating nearly half of the national income, the rural market is increasingly playing a very important and decisive role in the Indian marketing environment (Bargal, 2004). This market offers a cornucopia of opportunities to companies who venture to brave it. These rural markets exhibit linguistic, regional, cultural and economic disparities, and hence, are considered to be more complex to deal with than the urban markets. As branding can make or break a product, marketers have to take immense care in positioning a brand for rural market, as, often the traditional route to market entry and brand building employed in the urban markets do not provide the desired outcomes. Thus in order to make its presence felt corporate need to understand the needs and psyche of the rural consumers and tailor-made their offerings and the brand building initiatives according to the dynamics of the rural markets.Through this paper an attempt has been made to understand the ever changing dynamics, challenges and bottlenecks faced by the marketers and suggesting a gamut of innovative promotional and marketing activities which would help in creating distinct brand image and evoke positive brand associations.